Pengaruh Pemberian Sari Kurma Madu Terhadap Power His Kala I pada Ibu Bersalin di Klinik Az-Zahrah Satibih Cikarang Barat - Purwanti, Purwanti; Tridiyawati, Feva (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Every day in Indonesia 38 mothers die due to diseases/complications related to pregnancy and childbirth. (WHO, 2019). The maternal mortality rate in Indonesia in 2019 was 306/100,000 KH. This figure has decreased compared to the 2012 SDKI, namely 359/100,000 KH (Central Statistics Agency, 2017). The main cause of maternal death is approximately 75% due to postpartum bleeding, postpartum infection, pre-eclampsia/eclampsia, prolonged/obstructed labor and unsafe abortion. Most maternal deaths occur (34%) during the delivery period and the first 24 hours after delivery. If pain during labor is not treated, it will increase feelings of worry, tension, fear and stress. Odeng honey or honey that comes from the forest is a natural ingredient with nutritional content: fructose, vitamin C, vitamin B6, riboflavin, folate, iron, calcium, phosphorus. , zinc, magnesium, manganese, copper, sodium and selenium. To find out the effect of giving honey date juice on the strength of the first stage of women giving birth at the Az-zahrah Satibih clinic in 2023. This type of research is quantitative research, using quasi-experimental research methods, using 30 respondents consisting of 15 experimental group respondents. given honey date juice at the time of delivery, and 15 people in the control group who were not given honey date juice at the time of delivery. The average intensity of the Power of Labor in the first active phase of labor after administering Honey Date Juice was 6.71 with a standard deviation of 1.32. The intensity of Power His of labor in the first stage of active phase before administering Honey Date Sari was 5.00 with a standard deviation of 1.71. Meanwhile, the dependent T-test results obtained a p-value of 0.000. Because the p-value is 0.000 < α (0.05), it can be concluded that there is a significant effect on reducing the intensity of the Power His of labor during the first active phase before and after giving Honey Date Sari. There is an effect of giving Honey Date Juice on the duration and Power of HIS in the first stage of labor in women giving birth at the Az-Zahrah Satibih Clinic in 2023. It is hoped that giving Honey Date Juice during labor can be implemented in women giving birth, especially to reduce pain and improve HIS. Keywords: Honey Date Juice, His, Childbirth    ABSTRAK Setiap hari di Indonesia ada 38 ibu yang meninggal akibat penyakit/komplikasi terkait kehamilan dan persalinan. (WHO, 2019). Angka kematian ibu di Indonesia pada tahun 2019 yaitu 306/100.000 KH. Angka ini menurun bila dibandingkan pada SDKI tahun 2012 yaitu 359/100.000 KH (Badan Pusat Statistik, 2017). Penyebab utama kematian ibu kira-kira 75% disebabkan perdarahan pasca salin, infeksi pasca salin, pre eclampsia/ecklampsia, partus lama/macet dan aborsi yang tidak aman. Kematian maternal terjadi paling banyak (34%) pada periode persalinan dan 24 jam pertama pasca persalinan. Nyeri pada persalinan apabila tidak diatasi maka akan meningkatkan rasa khawatir, tegang, takut dan stress Madu odeng atau madu yang berasal dari hutan merupakan bahan alami dengan kandungan nutrisi : fruktosa, vitamin C, vitamin B6, riboflavin, folat, zat besi, kalsium, forsfor, zinc, magnesium, mangan, tembaga, natrium dan selenium. Untuk mengetahui Pengaruh Pemberian Sari Kurma Madu Terhadap Power His Kala I pada Ibu Bersalin di klinik Az-zahrah Satibih Tahun 2023. Jenis iipenelitian iiini iiadalah iipenelitian iikuantitatif, iimenggunakan iimetode iipenelitian ii quasi-eksperimentalI, menggunakan 30 responden yang terdiri dari 15 responden kelompok eksperimen yang diberikan sari kurma madu pada saat persalinan, dan 15 orang kelompok kontrol yang tidak diberikan sari kurma madu pada saat persalinan. Rata-rata intensitas Power His persalinan kala I fase aktif sesudah dilakukan pemberian Sari Kurma Madu adalah 6,71 dengan standar deviasi 1,32. Adapun intensitas Power His persalinan kala I fase aktif sebelum dilakukan pemberian Sari Kurma Madu adalah 5,00 dengan standar deviasi 1,71. Sedangkan Hasil Uji-T dependen diperoleh p-value sebesar 0,000. Karena p-value 0,000 < α (0,05) maka dapat disimpulkan ada pengaruh yang signifikan terhadap penurunan intensitas Power His persalinanan kala I fase aktif sebelum dan sesudah dilakukan pemberian Sari Kurma Madu. Ada pengaruh pemberian Sari Kurma Madu terhadap durasi dan Power His dalam persalinan kala I pada ibu bersalin di Klinik Az-zahrah Satibih Tahun 2023. Diharapkan pemberian sari kurma madu pada saat persalinan iidapat diimplementasikan iipada iiibu iibersalin, iikhususnya iiuntuk iimengurangi nyeri dan memperbaiki HIS Kata Kunci: Sari Kurma Madu, His, Persalinan